2012
DOI: 10.2478/s11536-011-0138-6
|View full text |Cite
|
Sign up to set email alerts
|

Normalized gait parameters in NDT-Bobath post-stroke gait rehabilitation

Abstract: AbstractThe aim of the research was to evaluate the results of NDT-Bobath method in gait re-education of adult patients after ischemic stroke using normalized parameters of gait. The investigation group consisted of 60 patients, all sufferers of an ischemic stroke, and participated in a rehabilitation program: 10 sessions of NDT-Bobath therapy through 2 weeks (ten days of the therapy). Normalized parameters of gait were calculated based on anthropometric measures of patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
1
6
0
5
Order By: Relevance
“…The study by Kılınç et al (2016) provided evidence that NDTBobath-based rehabilitation improved walking ability in post-stroke patients more than traditional therapy [5]. The limited evidence (due to lack of a reference group) of efficiency of the NDT-Bobath method in gait reeducation in adult post-stroke patients was described previously in several studies [1,5,10,[12][13][14][15]19]. Results described in this article are similar to the aforementioned, but constitute stronger evidence.…”
Section: Discussionsupporting
confidence: 67%
“…The study by Kılınç et al (2016) provided evidence that NDTBobath-based rehabilitation improved walking ability in post-stroke patients more than traditional therapy [5]. The limited evidence (due to lack of a reference group) of efficiency of the NDT-Bobath method in gait reeducation in adult post-stroke patients was described previously in several studies [1,5,10,[12][13][14][15]19]. Results described in this article are similar to the aforementioned, but constitute stronger evidence.…”
Section: Discussionsupporting
confidence: 67%
“…zastosowanie specyficznej hamującej mobilizacji) lub zwiększenie płaszczyzny podporu; zwiększenie obniżonego napięcia mięśniowego (np. przez oklepywanie -tapping) [12], d) facylitacja (ułatwianie) jest to sposób postępowania mający na celu prowadzenie, wspomaganie, a także w miarę potrzeby wykonanie ruchu za pacjenta; ułatwianie obejmuj: wsparcie zapoczątkowania ruchu, zmiany pozycji, ruchów zbliżonych do fizjologicznych; można tego dokonać poprzez handling (pacjent i terapeuta poruszają się razem), a także dzięki sytuacjom lub zadaniom (powinny one mieć znaczenie, być wartościowe dla pacjenta, by chętnie je wykonywał) oraz przez otaczające pacjenta środowisko (np. wyższe ustawienie leżanki ułatwia przejście z siadu do wstania) [12,13] (ryc.…”
Section: ćWiczenie VII Neuro Developmental Treatment -Bobathunclassified
“…przez oklepywanie -tapping) [12], d) facylitacja (ułatwianie) jest to sposób postępowania mający na celu prowadzenie, wspomaganie, a także w miarę potrzeby wykonanie ruchu za pacjenta; ułatwianie obejmuj: wsparcie zapoczątkowania ruchu, zmiany pozycji, ruchów zbliżonych do fizjologicznych; można tego dokonać poprzez handling (pacjent i terapeuta poruszają się razem), a także dzięki sytuacjom lub zadaniom (powinny one mieć znaczenie, być wartościowe dla pacjenta, by chętnie je wykonywał) oraz przez otaczające pacjenta środowisko (np. wyższe ustawienie leżanki ułatwia przejście z siadu do wstania) [12,13] (ryc. 6), e) w celu wykonania prawidłowego ruchu należy stosować następującą kolejność działań: odbudowa liniowości (terapeuta powinien ustawić wszystkie elementy ciała pacjenta w osi i w razie potrzeby wspomagać jej utrzymanie--można użyć do tego zewnętrznych pomocy, takich jak poduszki, kliny itp.…”
Section: ćWiczenie VII Neuro Developmental Treatment -Bobathunclassified
“…Of the studies investigating the clinical application of the Bobath concept, Øygard et al [41] reported the demographics of the treating therapist as a clinical specialist and an IBITA certified Bobath Basic Course Instructor. Mikołajewska [39] reported the therapists were IBITA Basic or Advanced level. Neither Kurosu et al [37] and Jelica et al [38], nor Ilett [40] reported the demographics of the treating therapists.…”
Section: Study Fidelitymentioning
confidence: 99%
“…Neither of these studies reported follow-up data. The case series Mikolajewska [39] reported a gait measure constructed for the study.…”
Section: Measurementmentioning
confidence: 99%